2010
DOI: 10.1055/s-0030-1250054
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Diosgenin Content in Medicinal Plants with Enzyme-Linked Immunosorbent Assay

Abstract: Many medicinal plants contain diosgenin, which has a significant medicinal value. However, there is currently no effective and rapid analytical method to determine the diosgenin content of plants or products. In the present work we have developed an indirect competitive enzyme-linked immunosorbent assay (ELISA) for the quantitative determination of diosgenin in herbal medicines. Diosgenin was conjugated with bovine serum albumin (BSA) for immunization. A polyclonal antibody developed in rabbits against a diosg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In this field, Li et al [129] developed an indirect competitive ELISA method to quantify diosgenin, namely, in Paris and Dioscorea species. The diosgenin molecule, which is too small to be considered an immunogen, was conjugated with bovine serum albumin (BSA) to create the immunization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this field, Li et al [129] developed an indirect competitive ELISA method to quantify diosgenin, namely, in Paris and Dioscorea species. The diosgenin molecule, which is too small to be considered an immunogen, was conjugated with bovine serum albumin (BSA) to create the immunization.…”
Section: Methodsmentioning
confidence: 99%
“…Then, from rabbits, a specific polyclonal antibody was developed against diosgenin-BSA conjugate. This method allowed a screening of several Chinese plants which have diosgenin as component [129]. A similar strategy was also developed to detect and quantify sarsasapogenin, a steroidal sapogenin structurally similar to diosgenin.…”
Section: Methodsmentioning
confidence: 99%
“…A variety of chemical constituents in Dioscorea species have been reported, comprising diterpenoids, flavonoids, phenanthrenes, sterols, steroidal saponins and stilbenes (Yang et al , ). Among these constituents, steroidal saponins, representative secondary metabolites of Dioscorea species, are being used to control the quality of botanical products or dietary supplements containing Disocorea species (Liu et al , ; Li et al , ). Thus, there seems to be a great need for an efficient separation method for steroidal saponins of Dioscorea species as these compounds may be utilised for pharmacological probes and quality control of botanical preparations (Li et al , ; Lin et al , ; Liu et al , ; Lin and Yang, ).…”
Section: Introductionmentioning
confidence: 99%
“…The content of diosgenin in Medicinal Plants could be determinated accurately by enzyme-linked immunosorbent assay or a micellar electrokinetic capillary chromatographic (MECC) (J. Li et al, 2010 ; N. Wang et al, 2019 ), and the water contents in diosgenin could be assayed with high accuracy using the mathematical model of near-infrared spectroscopy technology (M. Zhang et al, 2019 ). For the past few years, the biological activities of diosgenin has drawn much attention by studied in vivo and in vitro ( Leger et al, 2004 ; J.; Liagre et al, 2004 ; M. J.; Liu et al, 2005 ; Liagre et al, 2004 ; Srinivasan et al, 2009 ; Li et al, 2010 ; Ru et al, 2014 ; Chao et al, 2017 ; Qiao et al, 2018 ; Kessler et al, 2019 ; N.; Wang et al, 2019 ; M. Zhang et al, 2019 ; Mohamadi-Zarch et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… Li et al, 2010 ; N. Wang et al, 2019 ), and the water contents in diosgenin could be assayed with high accuracy using the mathematical model of near-infrared spectroscopy technology (M. Zhang et al, 2019 ). For the past few years, the biological activities of diosgenin has drawn much attention by studied in vivo and in vitro ( Leger et al, 2004 ; J.; Liagre et al, 2004 ; M. J.; Liu et al, 2005 ; Liagre et al, 2004 ; Srinivasan et al, 2009 ; Li et al, 2010 ; Ru et al, 2014 ; Chao et al, 2017 ; Qiao et al, 2018 ; Kessler et al, 2019 ; N.; Wang et al, 2019 ; M. Zhang et al, 2019 ; Mohamadi-Zarch et al, 2020 ). In previous studies, we found that diosgenin ( Mu et al, 2012 ) promoted apoptosis of human primary thyroid cells under the action of IGF-1 through the caspase signaling pathway, but its specific mechanism is not clear.…”
Section: Discussionmentioning
confidence: 99%